2022
DOI: 10.3390/land11112063
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Small-Scale Recirculating Aquaculture System for Sustainable (Peri-)Urban Farming in Sub-Saharan Africa: A Nigerian Perspective

Abstract: The (peri-)urban population in developing countries, especially sub-Saharan Africa, is rapidly increasing. As towns and cities grow, so does the demand for fish protein. While flow-through aquaculture can provide fresh, healthy and nutritious fish protein, it is plagued by extensive land requirements as well as effluent discharge and is thus unsuitable for city regions. Alternatively, small-scale Recirculating Aquaculture Systems (RAS) could improve food and nutritional security and livelihoods as well as redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Some species present cannibalism, so it is preferable to culture at low stocking densities (Blaylock et al, 2021). Besides, producing at high stocking densities needs a greater effort to maintain a good water quality (Benjamin et al, 2022) and cover the oxygen demand (it may be one of the most important inputs) (Baylar et al, 2008), which affects the profitability of the culture. However, this depends on the culture regimes and conditions of each producer (Ellis et al, 2002; Turnbull et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some species present cannibalism, so it is preferable to culture at low stocking densities (Blaylock et al, 2021). Besides, producing at high stocking densities needs a greater effort to maintain a good water quality (Benjamin et al, 2022) and cover the oxygen demand (it may be one of the most important inputs) (Baylar et al, 2008), which affects the profitability of the culture. However, this depends on the culture regimes and conditions of each producer (Ellis et al, 2002; Turnbull et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This system in a small scale is technically and financially feasible (Tokunaga et al, 2015) with efficient filtration and labor with aquaculture skill and appropriate aquaculture management (Benjamin et al, 2022). However, to produce more fish per area, the aquaponics system more promising with extra harvest comes from hydroponic vegetables.…”
Section: Parametersmentioning
confidence: 99%
“…Because RAS require more technological infrastructure than open pond systems, the energy costs of RAS have previously been identified as important restraints that may prevent this technology from being widely used (Singh and Marsh, 1996). Benjamin et al 2022 reported that it is critical to have access to appropriate equipment and inputs, as well as energy for the recirculating system. Moreover, the Indian government intends to develop 1178 recirculatory aquaculture system units by 2025, with a focus on Uttar Pradesh, Andhra Pradesh, Haryana, and Punjab (Anonymous, 2020).…”
Section: Introductionmentioning
confidence: 99%